Chemical Composition, Physicochemical, and Pharmacokinetics Profile of Custard Apple Leaf (Annona squamosa) Essential Oil Extract - Khrisna Pangeran; Khairul Anam; Dewi Kusrini (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
This study investigates the effects of different drying methods on the chemical composition, physicochemical characteristics, and pharmacokinetic properties of custard apple (Annona squamosa) leaf essential oils. The research also evaluates how these drying techniques influence the yield and quality of the oils, with particular emphasis on terpenoid content and their pharmacological relevance. Fresh custard apple leaves were subjected to four drying methods: shade drying, sun drying, oven drying at 45°C, and air conditioning (AC) drying at 20°C. Essential oils were extracted through steam distillation and analyzed using GC–MS to determine their chemical constituents. Various physicochemical parameters, including refractive index, specific gravity, acid value, and saponification value, were measured. Pharmacokinetic properties were assessed using the pkCSM online tool, while network visualization was performed via STRING.db. The drying methods significantly affected the essential oil yield, with oven drying producing the highest yield. Based on physicochemical analysis, shade drying resulted in the highest acid and ester values. The chemical profiles varied across treatments, with trans-β-caryophyllene, germacrene D, and α-humulene identified as the dominant compounds in all samples. Network pharmacology analysis indicated that CYP2C9 and CYP2C19 play critical roles in optimizing personalized therapy by minimizing adverse effects and enhancing drug efficacy across various diseases.